2013
DOI: 10.1073/pnas.1316009110
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic programming contributes to the genomic drift evolution of the F-Box protein superfamily in Arabidopsis

Abstract: Comparisons within expanding sequence databases have revealed a dynamic interplay among genomic and epigenomic forces in driving plant evolution. Such forces are especially obvious within the F-Box (FBX) superfamily, one of the largest and most polymorphic gene families in land plants, where its frequent lineagespecific expansions and contractions provide an excellent model to assess how genetic variation impacted gene function before and after speciation. Previous phylogenetic comparisons based on orthology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 32 publications
(72 reference statements)
4
50
0
Order By: Relevance
“…Markov clustering algorithm (MCL) tries to simulate a stochastic flow within the network structure, strengthening the flow where nodes are highly interconnected and weakening it in other regions until the flow process stabilizes [74]. MCL has found great popularity in network biology and has been used to characterize protein families within protein networks [75], detect orthologous and homologous groups [76], predict protein complexes from protein interaction networks [77], find gene clusters base on expression profiles [78], and to find clusters of putative pathogens and growth-promoting bacteria in phyllosphere microbiome [23].…”
Section: Topological Clustering Methods For Partitioning Data Into Bimentioning
confidence: 99%
“…Markov clustering algorithm (MCL) tries to simulate a stochastic flow within the network structure, strengthening the flow where nodes are highly interconnected and weakening it in other regions until the flow process stabilizes [74]. MCL has found great popularity in network biology and has been used to characterize protein families within protein networks [75], detect orthologous and homologous groups [76], predict protein complexes from protein interaction networks [77], find gene clusters base on expression profiles [78], and to find clusters of putative pathogens and growth-promoting bacteria in phyllosphere microbiome [23].…”
Section: Topological Clustering Methods For Partitioning Data Into Bimentioning
confidence: 99%
“…Tandemly duplicated genes arising from unequal crossover can also exhibit substantial epigenetic diversity. The large family of F-box proteins in Arabidopsis provides evidence for diversity of chromatin states within complex loci containing these genes (Hua et al, 2013).…”
Section: Chromatin-based Long-term Contributions To Regulatory Diversmentioning
confidence: 99%
“…Newly synthesized members in a family have been commonly recognized to experience either pseudogenization or fixation in a genome through four processes: 1) conservation if gene dosage is beneficial [1], 2) neofunctionalization if a novel function is acquired in one copy [1], 3) subfunctionalization if daughter copies split the function of the ancestral copy [7], or 4) specialization if all daughter copies perform new functions differing from their ancient copy [8]. Previous studies have suggested that dosage-balance constraints guarded duplicated copies against loss by determining the stoichiometry of duplicated products [9,10]. Interestingly, families involving different cellular functions have various birth over death ratios.…”
Section: Introductionmentioning
confidence: 99%
“…15 many biological laboratories are not yet able to take full advantage of the power of wholegenome sequencing because of the lack of the bioinformatic tools and/or skills.While many state-of-the-art bioinformatic tools have been developed to annotate genomes u, our studies have shown that superfamily members were often missing in various accomplished genome projects [5,6] (Tables 3 and 4). Studying gene duplications of a family across genomes can shed light on the evolutionary and functional mechanisms of intracellular regulatory pathways [4,6,10]. Yet, a biased conclusion could be made if a comprehensive understanding of the members of a gene family in genomes is not achieved.…”
mentioning
confidence: 99%